Pengaruh Struktur Modal, Kepemilikan Manajerial, Kepemilikan Institusional, dan Kebijakan Dividen Terhadap Nilai Perusahaan - Fiqriah Dinul Qoyyimah; Nursiam (Paradoks : Jurnal Ilmu Ekonomi, 2025)
Indonesia’s food and beverage industry presents a promising outlook for investment. From 2020 to 2021, the industry grew by 2.54%, reaching a value of Rp775.1 trillion. It contributed 6.61% to the national GDP, amounting to Rp1.12 quadrillion. This sector also accounted for 38.05% of the non-oil and gas processing industry. As interest in the sector continues to rise, competition is becoming increasingly intense—evidenced by the realization of investment reaching Rp85.10 trillion in 2023. Against this backdrop, the present study explores how capital structure (Debt to Equity Ratio/DER), managerial ownership, institutional ownership, and dividend policy (Dividend Payout Ratio/DPR) influence firm value, measured using the Price to Book Value (PBV). The analysis targets food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Using purposive sampling, 20 companies were selected from a population of 71, resulting in 60 observations. Employing secondary data and multiple linear regression (SPSS v25), the study finds that managerial and institutional ownership significantly impact firm value, while capital structure and dividend policy do not. These findings highlight the greater importance of ownership structure in enhancing firm value within this competitive sector.